Differentiation of Aerobacter-Klebsiella Isolated from Sugarcane - Nunez, William J. (1968)
Three hundred and eighty-four isolates were obtained in the completed test portion of the most probable number determinations of coliforms in sugarcane sources. Of these isolates, 88% were of the (- - + +) indole, methyl red, Voges-Proskauer, citrate (IMViC) type and were identified as Aerobacter aerogenes according to the protocol of the American Public Health Association (1). Employing 359 of these cultures, a comparative biochemical, serological, and pathogenicity study was carried out with Klebsiella pneumoniae CDC no. 2211-66 type 9. More than 86% of the organisms tested gave biochemical reactions typical of K. pneumoniae. Of the other isolates, 2% were Enterobacter aerogenes, and the remaining 12% were identified as atypical, nonmotile IMViC types. Comparable agglutination titers were also observed between A. aerogenes and the CDC strain of K. pneumoniae when several randomly selected sugarcane strains were reacted with prepared K. pneumoniae whole cell antiserum. Neither the K. pneumoniae reference organism nor selected sugarcane isolates displayed pathogenicity for mice. On the basis of all the analyses performed, it was suggested that such organisms be classified as K. pneumoniae.